University accountability practices in Mainland China and Hong Kong: a comparative analysis / Rui Yang, Lesley Vidovich and Jan Currie - Vidovich, Lesley; Currie, Jan (ACRULeT, Faculty of Education & UiTM Press, 2007)
This article reports findings from research about the tensions between global commonalities and localised differences in accountability policies and practices in Mainland China and Hong Kong. Based on empirical data, it indicates complex and dynamic interrelationships in globalising processes. There is resentment among academics in both societies toward the externally derived accountability practices and China and Hong Kong have both failed to strike a balance between the state, markets and universities. The findings remind us again of the crucial importance of local contexts in international policy borrowing. The theoretical framework adopted in this article brings together a hybrid of critical and post-structuralist perspectives to inform the analysis of policy, and allows for a macro or ‘bigger picture’ at global, regional and national levels, as well as micro-level interactions within individual institutions to be examined simultaneously. In-depth understanding was gained by collecting data in case study universities in different settings. Both documentary and interview data were collected from each case study institution. Quotes are used extensively to allow respondents’ voices to be heard, and an audit trail is provided with respondents coded for each institution.